Trademark Law An Open-Source Casebook - Beebe, Barton; Desmarais, John M. (Open textbook library., 2020)
Trademark Law: An Open-Source Casebook is a free, “open” textbook designed for a four-credit trademark course, which is what I teach at NYU School of Law. Model syllabi for four-credit and three-credit courses are available in the Faculty Resources section of this website.